2022
DOI: 10.3390/biom13010066
|View full text |Cite
|
Sign up to set email alerts
|

Human Alpha-1 Antitrypsin Attenuates ENaC and MARCKS and Lowers Blood Pressure in Hypertensive Diabetic db/db Mice

Abstract: Hypertension may develop before or after the onset of diabetes and it is known to increase the risk of developing diabetic nephropathy. Alpha-1 antitrypsin (AAT) is a multi-functional protein with beneficial effects in various diseases but its role in reducing blood pressure in the diabetic kidney has not been thoroughly studied. Like blood pressure, epithelial sodium channels (ENaC) and its adaptor protein myristoylated alanine-rich C-kinase substrate (MARCKS) are regulated by circadian rhythms. Our hypothesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 56 publications
0
6
0
Order By: Relevance
“…Several epithelial transport mechanisms have been studied in the context of the induction and maintenance of salt-sensitive hypertension. Multiple studies have shown db/db mice develop hypertension upon salt-loading [ 41 , 42 , 43 , 44 ]. A study by Scindia et al showed that metformin mitigated high blood pressure in hypertensive diabetic db/db mice in a mechanism involving the attenuation of renal ENaC [ 43 ].…”
Section: Salt-sensitive Hypertension and Enrichment Of Blood-pressure...mentioning
confidence: 99%
See 4 more Smart Citations
“…Several epithelial transport mechanisms have been studied in the context of the induction and maintenance of salt-sensitive hypertension. Multiple studies have shown db/db mice develop hypertension upon salt-loading [ 41 , 42 , 43 , 44 ]. A study by Scindia et al showed that metformin mitigated high blood pressure in hypertensive diabetic db/db mice in a mechanism involving the attenuation of renal ENaC [ 43 ].…”
Section: Salt-sensitive Hypertension and Enrichment Of Blood-pressure...mentioning
confidence: 99%
“…A study by Scindia et al showed that metformin mitigated high blood pressure in hypertensive diabetic db/db mice in a mechanism involving the attenuation of renal ENaC [ 43 ]. A study by Lugo et al showed that alpha-1 antitrypsin (AAT) treatment by intraperitoneal injection normalized blood pressure in salt-loaded hypertensive diabetic db/db mice in a mechanism involving the attenuation of renal ENaC and MARCKS protein expression [ 42 ].…”
Section: Salt-sensitive Hypertension and Enrichment Of Blood-pressure...mentioning
confidence: 99%
See 3 more Smart Citations